2014
DOI: 10.5901/mjss.2014.v5n16p162
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tourist Arrival and Foreign Exchange Earnings: The Case for Bangladesh

Abstract: Tourism is one of the promising sectors for Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This panel data analysis highlighted that there is a bi-directional causality between tourism receipts and GDP especially in countries located in Europe, North America, Latin America and the Caribbean regions. Apart from that, Aktar et al (2014), based on the Cointegration techniques, observed that there is a long run relationship between tourism revenue and foreign exchange earnings. It is observed that, a large number of empirical studies have examined the impact of the tourism sector on economic growth, employment and also the negative and positive impacts of tourism in relation to society and culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This panel data analysis highlighted that there is a bi-directional causality between tourism receipts and GDP especially in countries located in Europe, North America, Latin America and the Caribbean regions. Apart from that, Aktar et al (2014), based on the Cointegration techniques, observed that there is a long run relationship between tourism revenue and foreign exchange earnings. It is observed that, a large number of empirical studies have examined the impact of the tourism sector on economic growth, employment and also the negative and positive impacts of tourism in relation to society and culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some conversely find the non-impact of the exchange rate to tourism demand equally in various origin-destination scenarios (Zheng, 2011). In particular, there also exists the long run relationship between tourism demand and foreign exchange earnings, (Ruane, 2014), (Vita, 2014) and (Aktar, 2014). Multiple exchange rate regime effect and support the importance of maintaining a relatively stable price to attract tourism arrivals.…”
Section: Reviewing Existing Empirical Studiesmentioning
confidence: 99%
“…Study found the rise of unemployment by 20 percent in some developing countries, and in some other countries tourism will be wipe out if the same situation continues for a year (UNCTAD, 2020). Aktar et al (2014) analyzed the relationship between tourist arrival and foreign exchange earnings in Bangladesh. Study used monthly time series data from 2004 to 2010 from Bangladesh Parjatan Corporation and Bangladesh Tourism Board.…”
Section: Introductionmentioning
confidence: 99%